Potential Anti-aging Components From Moringa oleifera Leaves Explored by Affinity Ultrafiltration With Multiple Drug Targets - Xu, Yongbing; Chen, Guilin; Guo, Mingquan (Frontiers in Nutrition, 2022)
Moringa oleifera (M. oleifera), widely used in tropical and sub-tropical regions, has been reported to possess good anti-aging benefits on the skincare. However, the potential bioactive components responsible for its anti-aging effects, including anti-collagenase, anti-elastase, and anti-hyaluronidase activities, have not been clarified so far. In this work, ethanol extracts of M. oleifera leaves were firstly conducted for anti-elastase and anti-collagenase activities in vitro by spectrophotometric and fluorometric assays. Then, multi-target bio-affinity ultrafiltration coupled to high-performance liquid chromatography-mass spectrometry (AUF-HPLC-MS) was applied to quickly screen anti-elastase, anti-collagenase and anti-hyaluronidase ligands in the extracts of M. oleifera leaves, and revealed that they possessed good activities against skin aging-related enzymes. Meanwhile, 10, 8 and 14 phytochemicals were screened out as the potential anti-elastase, anti-collagenase and anti-hyaluronidase ligands, respectively. Further confirmation of these potential bioactive components with anti-aging target enzymes was also implemented by molecule docking analysis. In conclusion, these results suggest that the M. oleifera leaves might be a very promising natural source of anti-aging agent for skincare, which can be further explored in the cosmetics and cosmeceutical industries combating aging and skin wrinkling.